Mensuração da competitividade de startups baseada em múltiplos fatores - Silva Júnior, Claudio Roberto (2021)
The intense transformation of the technological scenario, the advent of the intelligent industry, and the growing demand for high quality and innovation have further intensified the dispute within the market. The differential of the good offered is preponderant for the survival or death of the ventures, mainly for startups, early-stage businesses that obtain their competitive advantage in the high degree of novelty of their products and services. As these organizations are generally micro and small enterprises, they need a greater knowledge of their competitive power to be able to duel with larger and more established companies. In this sense, this research aims to develop a model capable of measuring the competitiveness of startups based on multiple factors. Measuring your competitive capacity allows startups to visualize your position in the current scenario vis-à-vis competitors and to direct your strategic actions to achieve competitive performance. As for the methodological procedures adopted, the present research is classified as exploratory, descriptive, and of an applied nature, using the inductive scientific method and a qualitative and quantitative approach, where the technical procedures include bibliographic, documentary research, systematic literature review, and multiple cases study. 35 Critical Success Factors (CSF) were identified in the literature grouped into 4 Fundamental Points of View (FPV), namely: organizational, human, environmental factors, and 4.0 technologies. For this, the assumptions of the Key Performance Indicators (KPI) were used, in addition to the application of the Fuzzy AHP method to weight the weights related to CSF and FPV. To obtain the modeling inputs, two data collection instruments were applied in 28 startups, to which the weightings of the CSF and FPV weights, the global performance, and the local performances of each FPV related to the competitiveness of the responding startups were returned. The results were discussed, also, simulations and improvement proposals were carried out based on data from a startup that obtained unsatisfactory global performance, considering three scenarios, to demonstrate the performance growth, based on improvement proposals of specific indicators. Also, the diagnostic tool NIC - Competitiveness of Startups was developed, using Microsoft Excel® software, capable of collecting and processing data regarding the level of competitive performance. About contributions, this research can be considered a starting point for discussions on the theme, in addition to providing decision-makers with a robust tool for assessing business competitiveness.